Zur Frage der rückschreitenden Denudation und des dynamischen Gleichgewichts bei morphologischen Vorgängen - Ahnert, Frank (ERDKUNDE, 1954)
This paper investigates whether and to what extent there is a general regression of denudational processes on slopes following laws similar to those governing the recession of a nidi point on a river. Using the example of slope development during a period of down cutting the author shows that the resulting changes in the slope gradient, as well as the changes in the velocity of mass movement, recede from the bottom of the slope regressively upwards. This recession from the bottom of the slope plays a decisive role in scarplands by determining the intensity of denudation on the slopes of the Zeugenberge (residual outliers, literally: witness mountains) situated far away from the river courses. These mass movements show a tendency towards an equilibrium between removal and supply of rock waste.